CLINICAL AND PHARMACOECONOMIC ANALYSIS OF CARBAPENEMS (MEROPENEM, IMIPENEM AND DORIPENEM) IN NOSOCOMIAL PNEUMONIA TREATMENT - I. I. Shteynberg (Фармакоэкономика, 2015)
the article presents the results of a retrospective study conducted in the period from 2008 to 2011 in Moscow’s hospitals. The aim of the study was to compare the clinical and pharmacoeconomical efficacy of carbapenems in nosocomial pneumonia treatment. The study included 87 patients divided into 3 groups according to the therapy (imipenem, meropenem, doripenem). There were no statistically significant differences in clinical efficacy of carbapenems. Pharmacoeconomic analysis showed more profitable use of imipenem.